2014
DOI: 10.1111/1747-0080.12135
|View full text |Cite
|
Sign up to set email alerts
|

Migration‐related influences on obesity among sub‐Saharan African migrant adolescents in Melbourne, Australia

Abstract: Aim:The aim of the present study was to examine migration-and socioeconomic-related influences on obesity among African migrant adolescents in Melbourne, Australia. Methods: Anthropometric data were collected from 99 parents and 100 adolescent offspring who also completed questionnaires eliciting demographic, socioeconomic and migration data. Multiple linear regressions were used to assess the relationship between migration-and socioeconomic-related factors and adolescent body mass index (BMI). Results: Only g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…A number of determinants were identified in this review, including parenting style, family functioning, family communication, and family type. Refugee parents reported poor family functioning and lack of discipline, which were associated with childhood obesity 56,77 . These findings support the literature, in which higher family functioning is associated with a more healthy BMI and active lifestyle among adolescents 92 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A number of determinants were identified in this review, including parenting style, family functioning, family communication, and family type. Refugee parents reported poor family functioning and lack of discipline, which were associated with childhood obesity 56,77 . These findings support the literature, in which higher family functioning is associated with a more healthy BMI and active lifestyle among adolescents 92 .…”
Section: Discussionsupporting
confidence: 83%
“…Half focused exclusively on the perception of parents regarding the diet and physical activity of their children; the remainder obtained insights from refugee children themselves. Half of the studies focused their research questions on acculturation as the main factor influencing diet change 18,28,29,54,56,69,70–72,74,76 . Three studies focused on food insecurity, particularly in terms of eating patterns among refugee children 22,23,71 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renzaho et al (2008) suggested that integrated or marginalized children had a higher BMI, while keeping the traditions of the origin countries among children of immigrants was associated with a lower risk of obesity. However, Griffith et al (2014) suggested that parental integration was negatively associated with BMI, while adolescents’ acculturation patterns were not significantly associated with their BMI. Notably, the target population was different in these two studies: children were 3–12 years of age in Renzaho et al (2008), while adolescents were studied in Griffith et al (2014).…”
Section: Resultsmentioning
confidence: 92%
“…Of the three studies that used a standardized acculturation scale, Cheah and Van Hook (2012) used a modified parent version of the Chinese Children Acculturation Scale to measure the acculturation level of Chinese and Korean parents toward American culture. Griffith et al (2014) used the Acculturation, Habits, and Interests Multicultural Scale for Adolescents to measure the acculturation pattern of both adolescents and their parents. While the Chinese Children Acculturation Scale used by Cheah and Van Hock et al (2012) was unidimensional and focused more on acculturation toward the host country, the Acculturation, Habits, and Interests Multicultural Scale for Adolescents measured both the assimilation to the host country and the maintenance of traditional culture and was therefore considered a bi-dimensional scale.…”
Section: Resultsmentioning
confidence: 99%